Retrotransposon-like nature of Tp1 elements: implications for the organisation of highly repetitive, hypermethylated DNA in the genome of Physarum polycephalum. - Rothnie, H M (1991)
The repetitive fraction of the genome of the eukaryotic slime mould Physarum polycephalum is dominated by the Tp1 family of highly repetitive retrotransposon-like sequences. Tp1 elements consist of two terminal direct repeats of 277bp which flank an internal domain of 8.3kb. They are the major sequence component in the hypermethylated (M+) fraction of the genome where they have been found exclusively in scrambled clusters of up to 50kb long. Scrambling is thought to have arisen by insertion of Tp1 into further copies of the same sequence. In the present study, sequence analysis of cloned Tp1 elements has revealed striking homologies of the predicted amino acid sequence to several highly conserved domains characteristic of retrotransposons. The relative order of the predicted coding regions indicates that Tp1 elements are more closely related to copia and Ty than to retroviruses. Self-integration and methylation of Tp1 elements may function to limit transposition frequency. Such mechanisms provide a possible explanation for the origin and organisation of M + DNA in the Physarum genome.